Ectopia Lentis Associated with Primary Congenital Glaucoma. Issue 4 (July 2013) - Azar, Georges; Dureau, Pascal; Barjol, Amandine; Edelson, Catherine; Bergès, Olivier; Caputo, Georges
Purpose: To describe 3 cases of ectopia lentis (EL) associated with primary congenital glaucoma (PCG) and differentiate between primary and secondary EL regarding pathogenesis. Methods: We reviewed the clinical charts of 3 children previously diagnosed with congenital glaucoma who developed secondary EL. The following points were noted: medical and surgical history, refraction, keratometry, corneal diameter, axial length (AL), intraocular pressure, and cup/disc ratio. Results: The 3 patients were respectively aged 12, 3, and 4 months. A trabeculectomy was performed in both eyes at 1-week interval in all cases. The EL was noted during follow-up controls. Lensectomy/vitrectomy was performed in 2 patients, in case of high astigmatism (>5.00 D) and/or the lens border visible in the pupillary area. Postoperative refraction was hyperopic. Conclusions: Ectopia lentis secondary to PCG should be differentiated from primary EL regarding pathogenesis. Anterior segment distension appears to be the principal mechanism in these cases. Postoperative hyperopia is observed despite the increased AL secondary to PCG. These biometric results are due to global distension of the globe, which also flattens the cornea with consequently lower refractive effect.